Barriers and enablers to meticillin-resistant Staphylococcus aureus admission screening in hospitals: a mixed-methods study. Issue 1 (January 2019) - Currie, K.; King, C.; McAloney-Kocaman, K.; Roberts, N.J.; MacDonald, J.; Dickson, A.; Cairns, S.; Khanna, N.; Flowers, P.; Reilly, J.; Price, L.
Summary: Background: To reduce the risk of transmission of meticillin-resistant Staphylococcus aureus (MRSA), international guidelines recommend admission screening to identify hospital patients at risk of colonization. However, routine monitoring indicates that optimum screening compliance levels are not always achieved. In order to enhance compliance, we must better understand those factors which influence staff screening behaviours. Aim: To identify factors which influence staff compliance with hospital MRSA screening policies. Methods: A sequential two-stage mixed-methods design applied constructs from normalization process theory and the theoretical domains framework to guide data collection and analysis. Initial qualitative findings informed subsequent development of a national cross-sectional survey of nursing staff ( N = 450). Multiple regression modelling identified which barriers and enablers best predict staff compliance. Findings: Three factors were significant in predicting optimum (>90%) compliance with MRSA screening: having MRSA screening routinized within the admission process; category of clinical area; feedback of MRSA screening compliance within the clinical area. Integration of data-sets indicated that organizational systems which 'make doing the right thing easy' influence compliance, as does local ward culture. Embedded values and beliefs regarding the relative (de)prioritization of MRSA screening are important. Conclusion: To our knowledge, this is the first study to provide original evidence of barriers and enablers to MRSA screening, applying both sociological and psychological theory. As antimicrobial resistance is a global health concern, these findings have international relevance for screening programmes. Future policy recommendations or behaviour change interventions, based on the insights presented here, could have significant impact upon improving screening compliance.